Research of coefficient of drying in the period of handing down speed of drying is for thin saw-timbers - Kopynets, Zoya; Biley, Petro (Forestry, Forest, Paper and Woodworking Industry, 2024)
It is set experimental researches, that process of drying of thin saw-timbers (S1=6…10 mm) from wood of oak takes place the low temperature modes in the period of handing down speed of drying. The process of drying was conducted the two stage modes with transitional humidity 25 %. From curve of drying determine coefficient of drying for every stage of the regime. After the mathematical processing of experimental data equalization is got for determination of coefficients of drying on the first and second stages of process.